A Pragmatics Study of Indirect Speech Acts in President Joko Widodo's State Address - Nurul Fitriani; Tri Pujiati (English Department - University of Sultan Ageng Tirtayasa, 2018)
Language is an inseparable part of our everyday lives. Language is the main tool used to transmit messages, to communicate ideas, thoughts, and opinions. Language is also said to be a vehicle of culture. It consists of the culture of communicating which implies that there are certain typical institutions in language activities. When people use a language, we can guess their culture, espoused values, or even their beliefs or religions. We also can understand their manners, way of thinking, and the honesty they have. Indirectness is a widely used conversational strategy. People tend to use indirect speech acts mainly in connection with politeness since they want to lessen the unpleasant message contained in requests and orders, for instance. The purpose of this paper is to obtain an overall understanding of indirect speech acts found in some State Address by the President of Republic of Indonesia, Joko Widodo, regarding various things. The President wants to convey diverse messages to the people through indirect speech acts, and at the same time, to increase the force of the message communicated.